Revealing the Genetic Impact of the Ottoman Occupation on Ethnic Groups of East-Central Europe and on the Roma Population of the Area - Bánfai, Zsolt; Melegh, Béla I.; Sümegi, Katalin; Hadzsiev, Kinga; Miseta, Attila; Kásler, Miklós; Melegh, Béla (Frontiers in Genetics, 2019)
History of East-Central Europe has been intertwined with the history of Turks in the past. A significant part of this region of Europe has been fallen under Ottoman control during the 150 years of Ottoman occupation in the 16-17th centuries. The presence of the Ottoman Empire affected this area not only culturally but also demographically. Romani people, largest ethnic minority of the East-Central European area, share an even more eventful past with Turkish people from the time of their migration throughout Eurasia and they were a notable ethnic group in East-Central Europe in the Ottoman era already. Relationship of Turks with East-Central European ethnic groups and with regional Roma ethnicity was investigated based on genome-wide autosomal single nucleotide polymorphism data. Population structure analysis, ancestry estimation, various formal tests of admixture and DNA segment analyses were carried out in order to shed light to the conclusion of these events on a genome-wide basis. Analyses show that the Ottoman occupation of Europe left detectable impact in the affected East-Central European area and shaped the ancestry of the Romani people as well. We estimate that the investigated European populations have an average identity-by-descent share of 0.61 with Turks, which is notable, compared to other European populations living in West and North Europe far from the affected area, and compared to the share of Sardinians, living isolated from these events. Admixture of Roma and Turks during the Ottoman rule show also high extent.